An integrated green biorefinery approach towards simultaneous recovery of pectin and polyphenols coupled with bioethanol production from waste pomegranate peels. (October 2018) - Talekar, Sachin; Patti, Antonio F.; Vijayraghavan, R.; Arora, Amit
Graphical abstract: Highlights: Integral biorefinery of fresh WPP incorporating ecofriendly hydrothermal processing. One pot recovery of WPP pectin (18.8–20.9%) and phenolics (10.6–11.8%) was achieved. Hydrothermal processing improved enzymatic hydrolysis of WPP residue. Fermentation of WPP residue hydrolysates yielded 80 g ethanol/kg WPP. Abstract: An integrated biorefinery, incorporating hydrothermal processing of waste pomegranate peels (WPP), was proposed for the acid and organic solvent-free simultaneous recovery of pectin and phenolics with bioethanol production. The hydrothermal treatment (HT) was optimized using Box-Behnken design and the maximum recovery of pectin (18.8–20.9%) and phenolics (10.6–11.8%) were obtained by hydrothermal treatment at 115 °C for 40 min with a liquid-solid ratio of 10. The WPP pectin was characterized by IR, 1 H NMR, and TGA which showed close similarity to commercial pectin. Depending on WPP cultivar type the degree of esterification, galacturonic acid content and molecular weight of pectin were in the range of 68–74%, 71–72%, and 131, 137–141, 538 Da, respectively. The recovered phenolics contained 57–60% punicalagin. Enzyme digestibility of WPP improved using HT with 177 g glucose produced per kg dry mass which was fermented to obtain 80 g ethanol with 88% of theoretical yield.